The ancient Greek Oneirology and the Muslim Interpretation Historical Survey of Two Different Interpretations of Dreams (Oneirologi Purba Yunani dan Interpretasi Islam Dua Kajian Sejarah Interpretasi Mimpi Yang Berbeza Menerokai) - Kopanski, Ataullah Bogdan (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
Abstract There is no agreement among psychologists on sources and outcomes of the dreams in human brain during sleep. Secularist scholars of Freudian school of psychoanalysis claim that human dreams reflect their highly subconscious libido. Jungian school of kollective Unbewessustes disputes such extreme sexualized opinions and highlights the fact that rather large “collective unconscious” than sexuality is shared by representatives of all human cultures. But even without advanced studies, we can risk to believe that our dreams often predict coming events. Artemidoros Daldianus from Ephesus, the second century CE Hellenistic author of Oneirokritikon believed that dreams are human mind’s mirrors of the future. His magnum opus on the art of interpretation of dreams was translated into Arabic by famous Nestorian ophthalmologist Hunayn ibn Ishaq (Iohannitus) of Bayt al-Hikmah during the reign of Abbasid caliphs Maymun and Mutawakkil. The Prophet Muhammad (s.a.w.) often interpreted his own and Sahabah’s dreams with perfect accuracy. In the Qur’an, especially in Surah 12: Yusuf, 36-37, 99-101, the dreams are vehicles of foretelling the future not only of individuals but also of whole nations and states. The paper is written from historical perspective of the Muslim interpretation of dreams which emphasizes the Islamic examination of human dreams in context of the primary sources to the ancient Greek oneiromancy, studied by the Muslim scholars in the early centuries of Islamic Civilization, and their contribution to development of modern oneirology. Keywords: Oneirology, Interpretation of Dreams, Artemidoros’ Oneirocritica, Islamic Ta‘bÊr. Abstrak Tidak ada sebarang persetujuan di kalangan ahli psikologi terhadap sumber dan hasil daripada mimpi di dalam otak manusia semasa tidur. Para sekular Sekolah Psikoanalisis Freud mendakwa bahawa mimpi manusia mencerminkan kesedaran libido. Sekolah Unbewessustes kollective Jungian pertikaikan pendapat seksual melampau tersebut dan menyerlahkan bahawa kebanyakkan kesedaran bukan daripada kesedaran libido dan didapati dalam semua budaya manusia. Tetapi walaupun tanpa kajian yang canggih, kita boleh mengambil risiko untuk mempercayai bahawa mimpi kita sering meramalkan peristiwa yang akan datang. Artemidoros Daldianus dari Efesus, pengarang Hellenistik Oneirokritikon abad kedua CE percaya bahawa mimpi mencerminkan masa depan manusia. Seni interpretasi mimpi beliau telah diterjemahkan ke dalam Bahasa Arab oleh pakar mata Nestorian terkenal Hunayn ibn Ishaq (Iohannitus) dari Bayt al-Hikmah pada zaman pemerintahan khalifah Abbasiyah Maymun dan Mutawakkil. Nabi Muhammad (s.a.w.) sering mentafsirkan mimpi sendiri dan sahabat secara tepat. Dalam Al-Qur'an, terutamanya dalam Surah 12: Yusuf, 36-37, 99-101, mimpi adalah kenderaan untuk meramalkan masa depan bukan sahaja seorang individu tetapi keseluruhan negara dan negeri. Kajian ini ditulis dari perspektif sejarah interpretasi mimpi Islam yang menekankan pemeriksaan mimpi manusia dalam Islam dalam konteks sumber utama oneiromancy purba Yunani yang dikaji oleh para ulama Islam di abad-abad awal tamadun Islam, dan sumbangan mereka kepada pembangunan oneirologi moden. Kata Kunci: Oneirologi, Interpretasi mimpi, Oneirocritica Artemidoros, Ta‘bÊr Islam.